2005
DOI: 10.1093/toxsci/kfi184
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid I: Time Course of Lipid Peroxidation Biomarkers, Liver Toxicity, and Valproic Acid Metabolite Levels in Rats

Abstract: A single dose of valproic acid (VPA), which is a widely used antiepileptic drug, is associated with oxidative stress in rats, as recently demonstrated by elevated levels of 15-F(2t)-isoprostane (15-F(2t)-IsoP). To determine whether there was a temporal relationship between VPA-associated oxidative stress and hepatotoxicity, adult male Sprague-Dawley rats were treated ip with VPA (500 mg/kg) or 0.9% saline (vehicle) once daily for 2, 4, 7, 10, or 14 days. Oxidative stress was assessed by determining plasma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
82
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 31 publications
16
82
0
1
Order By: Relevance
“…10 VPA increases oxidative stress in the rat model as measured by serum and liver levels of 15-F 2t -IsoP, which increased in a time-and dose-dependent manner after single and multiple VPA doses. 32,38 These results suggest that VPA treatment increases ROS levels and that the liver may be the source of lipid peroxidation. Our data show that children receiving VPA have significantly higher levels of urine 15-F 2t -IsoP than those treated with CBZ or CLB or control subjects receiving no medications.…”
Section: Discussionmentioning
confidence: 82%
“…10 VPA increases oxidative stress in the rat model as measured by serum and liver levels of 15-F 2t -IsoP, which increased in a time-and dose-dependent manner after single and multiple VPA doses. 32,38 These results suggest that VPA treatment increases ROS levels and that the liver may be the source of lipid peroxidation. Our data show that children receiving VPA have significantly higher levels of urine 15-F 2t -IsoP than those treated with CBZ or CLB or control subjects receiving no medications.…”
Section: Discussionmentioning
confidence: 82%
“…VPA has broad applications. For this reason, the side effects associated with VPA, especially hepatotoxicity, have aroused widespread global concern [5,6] . Abdominal ultrasound studies showed the presence of non-alcoholic fatty liver disease (NAFLD) in 61% of VPA-treated patients [7] , which suggested a high frequency of changes in asymptomatic hepatic steatosis induced by VPA.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the implication of an increased generation of free radicals and oxidative stress in the toxicity induction mechanism of VPA (Kiang et al, 2010;Zhang et al, 2010). Different mechanisms have been proposed to explain inhibition of mitochondrial function by VPA (Tong et al, 2005b;Chang and Abbott, 2006). CNS depression is the most common demonstration of toxicity, ranging in severity from mild drowsiness to profound coma and fatal cerebral oedema.…”
Section: Introductionmentioning
confidence: 99%